The post-conflict reconstruction of the Syrian Nation-State from december 2017 until 2021 - Gómez Terán, Diana Samanta (2019)
During the last six years the international community has witnessed the decline of the Syrian Arab Republic and how the war has consumed this state. Around the critics and the failed attempts of solution, the subject of the present investigation arises proposing the post-conflict reconstruction of the Syrian nation-state from December of 2017 until 2021. The investigation is sustained in the premises of the Theory of Conflicts to understand the complexity and the challenges of the case of Syria, which allows later mentioning the Theory of Peace to propose viable and sustainable solutions. The investigation begins its analysis reviewing the crisis in Syria and how the structural damages of the state; unleash a civil war that violently escalated until having irreparable consequences. The crisis in Syria is the conflict that most interventions has identified in recent times. That is why, in order to study the actors, it divides them according to the internal social constructions, the external allies of direct assistance and the agents of indirect participation throughout the conflict. After studying the different aspects of the crisis in Syria, the research finally establishes a reconstruction proposal for the nation-state. This solution suggests initiating in the areas that need immediate attention, to later identify conflict resolution mechanisms and finally, propose a reconstruction process that focuses on maintaining peace.